Treatment of Acute, Uncomplicated Urinary Tract Infections in Children: A Comparison of a Single Oral Dosage of Fosfomycin Against a Seven-Day Course of Ciprofloxacin - Ayesha Tariq, Saba Afzal Shaikh, Asfand Tariq, Zahid Anwar, Qamar Uz Zaman Shahzad, Reem Falah Al-Shammari (Pakistan Journal of Medical & Health Sciences, 2022)
Objective : Urinary tract infection is one of the commonest infections in the pediatric age group. The emergence of resistance to various antibiotics has posed many difficulties in treating such patients. This study has been done to compare the efficacy of fosfomycin & ciprofloxacin in pediatric Urinary tract infection (UTI). Study Design: Randomized Control study Place and Duration: Akhtar Saeed Medical College/ Farooq Hospital. July, 2021 to Dec, 2021 Methodology: This randomized controlled clinical trial is done at the Department of Pediatrics, Akhtar Saeed Medical College/ Farooq Hospital. One hundred and thirty individuals who met the criteria for UTI were recruited. The patients were split into two groups at random. Patients in Group A received 15–20mg/kg of oral Ciprofloxacin twice daily (BD) for 7 days, whereas those in Group B received 150–300mg/kg of oral fosfomycin all at once. Results: One-hundred and ten patients included in this trial. In group A mean age of the paties was 6.4±2.8 years and in group B patients had mean age 7.7±3.0 years. There were 35 males (63.6%) and 20 females (36.4%) in group A and in group B 33 males (60%) and 22 females (40%). As per effectiveness we found that fosfomycin was effective in 42 patients (76.4%) and ciprofloxacin was efficacious in 30 patients (54.5%) with p-value 0.016. Conclusion: When comparing the treatment of children with acute uncomplicated urinary tract infections, the results showed that a single oral dosage of fosfomycin was substantially more effective than ciprofloxacin. Keywords: Antibiotics, Resistance, uropathogens, paediatrics, UTI, gram-negative,